A highly linear RF mixer using gate-all-around junctionless transistor. Issue 2 (3rd April 2017) - Pandey, Sunil; Sahu, Chitrakant; Singh, Jawar
ABSTRACT: In this paper, we investigate the performance of a radio-frequency (RF) mixer based on single-silicon nanowire gate-all-around (GAA) junctionless field-effect transistor (JLFET). The main novelty in this work is the achievement of high linearity of RF mixer using band-to-band tunnelling phenomenon of GAA-JLFET. Using technology computer-aided design (TCAD) simulations, we extracted the value of unity-gain cut-off frequency of 420 GHz, which shows its potential for circuit applications in the extremely high-frequency regime. The harmonic-balanced simulations in Agilent advanced design system tool with an emphasis on the device-circuit interaction are used to analyse the RF mixer performance, such as output spectrum, 1-dB compression point, and conversion gain in comparison with 32-nm conventional n-metal oxide semiconductor transistor.